Kinematic and biomechanical responses of the spine to distraction surgery in children with early onset scoliosis: A 3-D finite element analysis - Pei, Baoqing; Lu, Da; Wu, Xueqing; Xu, Yangyang; Ma, Chenghao; Wu, Shuqin (Frontiers in Bioengineering and Biotechnology, 2022)
Periodical and consecutive distraction is an effective treatment for severe early onset scoliosis (EOS), which enables the spinal coronal and sagittal plane deformity correction. However, the rate of rod fractures and postoperative complications was still high mainly related to the distraction process. Previous studies have primarily investigated the maximum safe distraction force without a rod broken, neglecting the spinal re-imbalance and distraction energy consumption, which is equally vital to evaluate the operative value. This study aimed to reveal the kinematic and biomechanical responses occurring after spinal distraction surgery, which were affected by traditional bilateral fixation. The spinal models (C6-S1) before four distractions were reconstructed based on CT images and the growing rods were applied with the upward displacement load of 0-25 mm at an interval of 5 mm. Relationships between the distraction distance, the distraction force and the thoracic and lumbar Cobb angle were revealed, and the spinal displacement and rotation in three-dimensional directions were measured. The spinal overall imbalance would also happen during the distraction process even under the safe force, which was characterized by unexpected cervical lordosis and lateral displacement. Additionally, the law of diminishing return has been confirmed by comparing the distraction energy consumption in different distraction distances, which suggests that more attention paid to the spinal kinematic and biomechanical changes is better than to the distraction force. Notably, the selection of fixed segments significantly impacts the distraction force at the same distraction distance. Accordingly, some results could provide a better understanding of spinal distraction surgery.